Universities, Defamation and the Internet. - Vick, Douglas W.; Macpherson, Linda; Cooper, Sarah (Modern Law Review, 1999)
Examines the potential effect of defamation law on discourse over the Internet. Number of lawsuits arising out of the Internet communications that involved defamation claims; Advantages afforded claimants by English law; Potential liability of universities.